2022
DOI: 10.1177/19485506221077861
|View full text |Cite
|
Sign up to set email alerts
|

Hegemonic Masculinity Predicts Support for U.S. Political Figures Accused of Sexual Assault

Abstract: In three studies ( N = 886), we hypothesized and found that women’s and men’s endorsement of the culturally idealized form of masculinity, hegemonic masculinity (HM), predicted more positive evaluations of a political figure accused of sexual violence (Supreme Court Justice Kavanaugh) and more negative evaluations of the women who made accusations of sexual assault. HM predicted these evaluations over and above political party, gender, race, education, and sexism (Study 1), rape myth endorsement (Study 2), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Developmental work has shown that in middle childhood, girls become more aware of power and status at the societal level and often respond by shifting from idealizing the “girly-girl” to striving to be “one of the boys” ( Halim et al, 2011 ). By adolescence, girls tend to identify with masculinity ideology to a similar degree as boys ( Priess et al, 2009 ; Rogers et al, 2020 ) and in adulthood, women’s and men’s identification with hegemonic masculinity predicts important outcomes such as evaluations of politicians accused of sexual assault ( Schermerhorn et al, 2022 ). Our findings add to this body of work on the continued relevance of traditional masculinity ideology among all genders, suggesting that cultural beliefs and values for dominance and invulnerability in relationships can inform the needs adolescents seek to fulfill with social media.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental work has shown that in middle childhood, girls become more aware of power and status at the societal level and often respond by shifting from idealizing the “girly-girl” to striving to be “one of the boys” ( Halim et al, 2011 ). By adolescence, girls tend to identify with masculinity ideology to a similar degree as boys ( Priess et al, 2009 ; Rogers et al, 2020 ) and in adulthood, women’s and men’s identification with hegemonic masculinity predicts important outcomes such as evaluations of politicians accused of sexual assault ( Schermerhorn et al, 2022 ). Our findings add to this body of work on the continued relevance of traditional masculinity ideology among all genders, suggesting that cultural beliefs and values for dominance and invulnerability in relationships can inform the needs adolescents seek to fulfill with social media.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Woolf 's thesis about challenges to traditional gender relations leading to masculine self-assertion in politics, research clearly shows that masculinity has something to do with right-wing extremism. For example, Schermerhorn et al (2023) have shown that masculine hegemony beliefs substantially account for people's support for male political candidates who have been accused of sexual assault. They measured hegemonic masculinity using items from the Male Role Norms Scale assessing beliefs that men should seek power and status, show emotional and physical toughness, and avoid anything smacking of femininity (e.g., taking on roles or jobs typically done by women).…”
Section: What Is Gender Identity?mentioning
confidence: 99%
“…A clear example of the consequences of this model of masculinity being hegemonic is sexual violence (Haney, 2011;Javaid, 2018;Messerschmidt, 2020). There is different research that endorses this evidence and its consequences, Schermerhorn, Vescio & Lewis (2022) show, that due to the idealization of hegemonic masculinity, in many cases, political figures are accused of rape receive positive evaluations, while women who denounce receive negative evaluations. Another example, research conducted in South Africa by Jewkes and Morrell showed how men who follow this model of masculinity engage in risky sexual practices with a high degree of violence that exposes the women with whom they are in a relationship to HIV infection (2010).…”
Section: The Dichotomy Between Hegemonic Masculinity and Egalitarian ...mentioning
confidence: 99%